2009
DOI: 10.1007/s11235-009-9229-y
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of SWAN QoS model in MANETs with proactive and reactive routing: a simulation study

Abstract: In this article, one of the QoS models for MANETs-SWAN is studied under varying conditions to provide both quantitative and qualitative assessments of the applicability of the model in different scenarios. Results and analysis from NS-2 based simulation indicate that (i) realtime (RT) applications in SWAN-enabled mobile ad hoc networks experience low and stable delays under various traffic and mobility environment at the expense of best-effort (BE) traffic, (ii) SWAN model works compatibly with proactive as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Regular networks have been analyzed in [19,20] for stability and capacity, albeit with specific focus on capacity regions [19] or impact of buffer sizes [20]. Related work for our impact analysis methodology is sensitivity analysis, which has been studied using simulation [21], and analytically using Automated Differentiation techniques in [22]. Some of these works consider real-world aspects, but focus on specific protocols or issues (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Regular networks have been analyzed in [19,20] for stability and capacity, albeit with specific focus on capacity regions [19] or impact of buffer sizes [20]. Related work for our impact analysis methodology is sensitivity analysis, which has been studied using simulation [21], and analytically using Automated Differentiation techniques in [22]. Some of these works consider real-world aspects, but focus on specific protocols or issues (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…In [15], a hybrid approach (incorporating DiffServ) is proposed to achieve performance gain in most of the traffic load conditions using SWAN model. A comprehensive simulation study is reported in [16] that is based on the SWAN model in MANET environment. We can conclude that SWAN tries to maintain delay and bandwidth requirements of RT traffic by admission control of UDP traffic and rate control of TCP and UDP traffic.…”
Section: Swanmentioning
confidence: 99%